The Implementation of Online Learning During Covid-19 Pandemic: English Teachers’ Perceptions at Senior High Schools in South Aceh - Tathahira, Tathahira; Sriayu, Sriayu (Universitas Negeri Semarang, 2020)
This article illustrates the teachers’ perception in the implementation of online learning during Covid-19 crisis. Draw from qualitative approach this research interviewed eight English teachers from several senior high schools in South Aceh purposely. The result shown that WhatsApp became the main preferred social media to initiate the online learning and it has crucial role during the courses. The respondents also admit that they collect the materials from the internet as well as from students’ textbook, they even create such learning media by using familiar platform. Moreover, the poor internet connection, scarcity of smartphone ownership, and less good interaction and communication between students and teachers were also the main barriers amid the online learning. Finally, all respondents admit that they have several efforts and strategies to overcome these problems, e.g. print out the worksheet for students who do not have smartphone, gives less assignment for the students, and gives the assignment earlier so students will have much time to accomplish it properly. Abstrak Artikel ini menggambarkan persepsi para guru dalam mengimplementasikan pembelajaran dalam jaringan (daring) selama krisis Covid-19. Berangkat dari pendekatan kualitatif penelitian ini menginterviu delapan guru Bahasa Inggris dari beberapa Sekolah Menengah Atas (SMA) di Aceh Selatan dengan kriteria tertentu. Hasil penelitian menunjukkan bahwa WhatsApp menjadi media sosial yang paling dipilih untuk memulai pembelajaran daring dan perannya penting selama pembelajaran. Responden juga mengemukakan bahwa mereka memperoleh materi pembelajaran dari internet, selain juga tetap mendasarkan pada buku teks siswa, mereka bahkan membuat media pembelajaran menggunakan platform yang familier. Berikutnya, buruknya koneksi internet, kelangkaan kepemilikan telepon pintar, dan kurangnya interaksi dan komunikasi yang bagus antara siswa dan guru juga menjadi hambatan utama pembelajaran daring. Terakhir, semua responden mengemukakan bahwa mereka telah berupaya dan mengembangkan strategi untuk mengatasi masalah-masalah tersebut, antara lain mencetakkan lembar kerja siswa untuk siswa yang tidak memiliki telepon pintar, mengurangi pemberian tugas, dan memberikan tugas di awal waktu agar siswa memiliki waktu banyak untuk mengerjakannya dengan baik.